What Should Constitute a Health Related Quality of Life Scale for Parkinson’s Disease? - RAJEEV AGGARWAL; VINAY GOYAL; RAVINDRA MOHAN PANDEY; NAND KUMAR; SUMIT SINGH; GARIMA SHUKLA; MADHURI BEHARI (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Health Related Quality of Life (HRQoL) in Parkinson’s Disease (PD) lacks universally agreed definition and its components. A conceptual framework helps in understanding the essential domains and their inter-relationship while developing patient reported outcome measure. Aim: To construct a conceptual framework for developing HRQoL scale in PD. Materials and Methods: A panel of 7 experts extracted 6 major domains for measuring HRQoL in PD from literature review including 8 disease specific scales for PD, 2 books on quality of life, 5 websites, relevant articles; and content analysis of semistructured interviews of stakeholders (28 persons with PD, 6 caregivers and 9 clinicians). Extracted domains were subjected to consensus of stakeholders (7 persons with PD, 7 caregivers and 7 clinicians) on 7 point Likert scale. The panel constructed a conceptual framework and a definition of HRQoL in PD in context of available guidelines for developing patient reported outcome measures. Results: The extracted domains were physical, non motor symptom, psychological, family/social, finance and treatment domains. Median of all six domains on 7 point Likert scale was 7 and inter-quartile distance was <1 in consensus agreement. The conceptual framework consisted of indicator domains and causal domains. Indicator domains (physical, psychological, and social and family) estimate the influence of causal domains (motor symptoms, non motor symptoms, finance and treatment) on quality of life. The definition emphasizes upon the person’s perception of their symptoms and its impact on their lives. Conclusion: This study defined and developed a conceptual framework for HRQoL scale for PD.